IMPLEMENTASI KITAB WASHOYA DALAM PENGUATAN LITERASI UNTUK MENUMBUHKAN KARAKTER RELIGIUS PADA MATA PELAJARAN AKIDAH AKHLAK DI MI PLUS DARUSSAADAH LIRBOYO KEDIRI - Shodiqin; Allamsyah Hadi Wijaya; Ahmad Khoirul Mustamir; Moh. Irmawan Jauhari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The cultivation of religious character through Akidah Akhlak subjects is crucial in Islamic basic education institutions. This study aims to describe the implementation of the Washoya Book in strengthening religious literacy and its impact on the religious character of students at MI Plus Darussaadah Lirboyo Kediri. This research uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that: (1) The implementation of the Washoya Book is carried out through the planning of the Merdeka Curriculum integrated with the pesantren curriculum, using sorogan, ma'nai, and discussion methods. Evaluation is conducted periodically through mid-semester and end-of-semester exams. (2) The impact of using this book is an increase in students' religious literacy in reading Pegon Arabic texts and the internalization of religious character values such as obedience, politeness, and responsibility. This is strengthened by intensive supervision from assistant teachers. The integration of classical literature in formal primary education proves effective in building a strong religious foundation for students.